Análisis de la Estrategia Nacional de Electromovilidad como alternativa de política pública en el sistema de transporte público urbano de la Ciudad de Loja - Ortega Lima, Edwin Vicente (2022)
Public transport systems and their high dependence on fossil fuels, generate impacts of considerable magnitude on the health of people and the environment, due to the volume of CO2 they emit in their operation, and, which are evidenced worldwide in events such as: high temperatures, abnormal alluvial rainfall and melting glaciers. This situation keeps public and private actors, at the national and local levels, on alert to intervene in the public transport sector through the modernization and decarbonization of buses and taxis as a option to reduce the aforementioned impacts due to the use of fossil fuels (Mañez et al., 2018). Therefore, this research analyzes the National Strategy of Electromobility of Ecuador (ENEM) as a public policy in the urban public transport system of the city of Loja, to generate a baseline of knowledge, based on the local reality, through the application of research techniques such as bibliographic analysis and interviews with the key actors of electromobility, additional, this research presents a financial, environmental and social calculation. The main results show that the electrification of the urban public transport system of the City of Loja, based on the goals of the ENEM, generates a positive impact, measured by the environmental benefit due to the gases that are no longer emitted by the replaced taxis and buses. It is suggested that the GAD of Loja assume the leading role, to articulate municipal measures to facilitate transport operators to adopt the use of electric vehicles for passenger transport.